2010
DOI: 10.1523/jneurosci.5991-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporin A Has Direct Effects on Adult Neural Precursor Cells

Abstract: Multipotent, self-renewing neural stem cells and their progeny [collectively referred to as neural precursor cells (NPCs)] represent a population of cells with great promise for CNS repair. To effectively harness their potential for therapeutic applications, the factors that regulate NPC behavior and/or fate must be well understood. The ability of immunomodulatory molecules to affect NPC behavior is of interest because of recent work elucidating the complex interactions between the immune system and nervous sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
61
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 47 publications
(43 reference statements)
8
61
1
Order By: Relevance
“…Consistent with in vitro observations, in vivo administration of CsA to adult animals increased the numbers of NPCs within neurogenic niches lining the lateral ventricles 27 .…”
Section: Discussionsupporting
confidence: 84%
“…Consistent with in vitro observations, in vivo administration of CsA to adult animals increased the numbers of NPCs within neurogenic niches lining the lateral ventricles 27 .…”
Section: Discussionsupporting
confidence: 84%
“…Reasons for the unchanged neurogenesis and dendritogenesis after cyclosporine treatment in our experiments compared to previously published studies might include the use of higher cyclosporine doses in these studies and that experiments were performed with healthy animals. 15,16 However, although both groups of the cell therapy experiments received immunosuppression, we cannot completely rule out that cyclosporine A might confound our results because we performed no experiment that contains all 3 groups, NPC-treated animals and placebo-treated animals with and without immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…1,26 Recent research suggests that cyclosporine A affects neurogenesis and dendritic plasticity. 15,16,28 To address this issue, we performed experiments that compared animals treated with cyclosporine A with a daily dose of 10 mg/kg body weight and placebo. In these experiments, we found no significant differences between the 2 groups regarding functional recovery improvement, neurogenesis in the dentate gyrus, microglial activation, and dendritic regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of p53 promotes survival through downregulation of p53-upregulated modulator of apoptosis (PUMA) [100,102] . More recently it was found that cyclosporine A (CsA), a commonly used immunosuppressive drug, acts directly on NPCs to increase their survival without affecting cell cycle kinetics [103] . While the pro-survival mechanism has not been fully elucidated, the administration of CsA in vivo resulted in >2 fold increase in the size of the NPC pool in control mice.…”
Section: Promoting Survivalmentioning
confidence: 99%